DOUBLE MOLYBDATES-TUNGSTATES SYSTEM MR(EO4), WHERE M – NH4, Ag, Cu, Tl, R – TRIVALENT METAL, E – Mo, W: DOI: https://doi.org/10.17721/1728-2209.2018.1(55).4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
More than 120 double tungstates and molybdates of general formula MR(EO4), where M – NH4, Ag, Cu, Tl; R – trivalent metals, E – W, Mo; R – Bi (excepting compounds contained NH4), La – Lu, Y, Sc (excepting compounds contained Cu (I)), In (excepting compounds contained NH4 and Tungsten) were isolated by co-precipitating from aqua solutions, or by solid-phase synthesis. All above mentioned compounds were studied by chemical analysis, thermogravimetry, X-ray and IR spectroscopy.Different numbers structural types were discovered into rows double tungstates and molybdates of composition MR(EO4)2: NH4R(WO4)2 – 3; NH4R(MoO4)2 – 3; AgR(WO4)2 – 4; AgR(MoO4)2 – 5; CuR(WO4)2 – 3; CuR(MoO4)2 – 5; TlR(WO4)2 – 8; TlR(WO4)2 – 11.Most wide among of its are sheyelit CaWO4, types: of KY(MoO4)2, α-KNd(WO4)2, α-KY(WO4)2, of its structural-distorting modifications and structures similar for glazerit.The calculation of meaning ∆Ho298 MR(EO4)2, M – alkali metals, NH4, Cu, Ag; E – Mo, W, R – M (II) by method of Kaganyuk D.S. was executed. Dependence ∆Ho298 for 300 compounds from radii ratio of mono- and trieevalent metals wаs presented in form of diagrams, it was provided possibility to unite all compounds in only system, where wide areas broadening of structural types were determinated. This diagrams is showing boundaries of structural types, is foreseeing building of unknown like that compounds and is forecasting isomorphic substitution in double tangstats and molybdates of composition MR(EO4)2. It is necessary in processes of preparation of materials for lasers, colouring luminophores, catalyzers, semiconductors, segneto- and piezoelectrics and  other materials. It was designed the refined diagrams described regions of structural types of synthesized compounds existing. The formation regularities of different types of polymorphic modifications for crystal structures of the isolated compounds depending on the radii ratio of mono- and trivalent metals have been established. It was compiled a database for materials based on the studied compounds.
Keywords: double molybdates and tungstates of Ammonium, Silver, Copper(I), Thallium and trivalence metals, diagrams of structural types, perspectives of applied using.